Community resilience and land degradation in forest and shrubland socio-ecological systems: Evidence from Gorgoglione, Basilicata, Italy. (July 2015) - Kelly, Claire; Ferrara, Agostino; Wilson, Geoff A.; Ripullone, Francesco; Nolè, Angelo; Harmer, Nichola; Salvati, Luca
Highlights: Innovative approach for understanding community resilience. New insight into resilience/land degradation interface. Case study from a relatively unexplored region of EU. Multi-disciplinary article associated with large EU project. Abstract: Assessing the resilience of communities is assuming greater importance at a time of global economic upheaval, climatic and socio-demographic changes. The past 10–15 years have seen a significant increase in the number of studies addressing resilience issues at community level from a variety of perspectives, and although the resilience of communities in dealing with disturbance feature strongly in these studies, less work appears to have been undertaken at the interface between community resilience and land degradation. In addition, little attention has been paid to land degradation, desertification risk and community resilience at the forest–community interface, despite the fact that forest ecosystems represent one of the most important terrestrial biomes in terms of the ecosystem services and socio-economic benefits that they provide. Building on existing community resilience literature which highlights the importance of various socio-economic and political drivers for understanding community resilience, this paper analyses how economic, political, institutional, social, cultural and natural factors at community level affect the ability of communities to adapt and adjust decision-making pathways towards resilience. The paper will focus on the municipality of Gorgoglione (Basilicata, Italy), a typical Mediterranean forest and shrubland socio-ecological system characterised by a mixture of agricultural and forest landscapes prone to land degradation issues linked to both anthropogenic (deforestation, overgrazing, forest fires) and natural (soil erosion, droughts, climate aridity) causes. A mixed-method approach is used, drawing on quantitative and qualitative data across spatial levels and temporal scales to examine the complex interrelationships between community resilience, forest ecosystems and land degradation.